Exploration of Ethnomathematics at the Batu Tulis Site in Cipaku Village Purbalingga as a Mathematics Learning Resource - Akbar Fuadin; Abdelillah Jamous (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This research aims to explore mathematical concepts present in historical artifacts at the Batu Tulis Site in Cipaku Village, Purbalingga, as a source of learning mathematics through an ethnomathematics approach. The research method used is qualitative with an ethnographic approach. Data was collected through observation, interviews, and documentation. Observations were conducted by the researcher. Interviews were conducted with two informants: the manager of the Batu Tulis Site in Cipaku Village, who is also a cultural expert. Documentation was carried out during the observation process. The results of the research show that the Batu Tulis Site in Cipaku Village contains numerous cultural elements, as evidenced by the many historical artifacts, each with its own philosophical significance. In addition to cultural elements, mathematical concepts were also identified, such as geometric shapes found in the iron fence (rectangle), tiles (square), and wooden wheels (circle). The concept of angles is present in the statue of Dewa Wisnu (acute angle), houses (obtuse angle), and pillars (right angle). The concept of three-dimensional shapes is found in the watu kenong (sphere), genthong (cylinder), and stone inscriptions (irregular shapes). Geometric transformation concepts are evident in the statue of Dewi Welas Asih (translation), wooden wheels (rotation), floral motifs (reflection), and gamelan instruments (dilation). The concept of sets is found in gamelan instruments. The concept of lines is present in the inscriptions on the stone. The concept of similarity is found in the entrance gate. In addition to cultural elements and mathematical concepts, ethnomathematical activities were also identified at the Batu Tulis Site in Cipaku Village, including play activities, design and construction activities, measuring activities, and location-determining activities. The discovery of these ethnomathematical activities at the Batu Tulis Site in Cipaku Village can be utilized as a source for learning mathematics.